2021
DOI: 10.3389/fnut.2021.652767
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Choline-Enhanced Skin Immune Response of Juvenile Grass Carp Might Be Related to the STAT3 and NF-kB Signaling Pathway (Ctenopharyngodon idella)

Abstract: To investigate the effects and potential mechanisms of dietary choline on immune function in the skin of juvenile grass carp (Ctenopharyngodon idella), fish were fed different diets containing different levels of choline (142. 2, 407.4, 821.6, 1215.8, 1589.3, and 1996.6 mg/kg) for 70 d and then sampled after a 6-d challenge test. The results exhibited that dietary choline (1) advanced the contents of phosphatidylcholine (PC), betaine, and choline in grass carp skin (P < 0.05) and upregulated the mRNA ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…It has been demonstrated that choline exerted antiinflammatory effect in asthma patients. 30 Choline could also enhance the skin immune function in fish, 31 as well as improve the functionality of the immune system in dairy cows. 32 Thus, the declining of choline exposed to EMB was relevant to the impairment of immune function, which is the nearly coincide with the EMB-induced immunotoxicity results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that choline exerted antiinflammatory effect in asthma patients. 30 Choline could also enhance the skin immune function in fish, 31 as well as improve the functionality of the immune system in dairy cows. 32 Thus, the declining of choline exposed to EMB was relevant to the impairment of immune function, which is the nearly coincide with the EMB-induced immunotoxicity results.…”
Section: Discussionmentioning
confidence: 99%
“…CD206 and Arginase-I are markers of macrophage polarization 24 , 25 . Previous studies have shown that STAT can inhibit nuclear factor kappaB (NF-κB) expression through the CD206/Arginase-I/IL-4/IL-10 signaling pathway 26 29 . Importantly, the activation of the NFκB-dependent inflammatory signaling pathway drives SHP2 gene expression 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Dietary methionine has been linked to direct dermatologic impact, with methionine supplementation linked to improved coat and skin characteristics and reduction of allergic dermatitis in domestic animals ( Zhang et al., 2013 ). While choline’s role in the skin is less-well established, dietary enrichment with choline is associated with enhanced skin immune function and recession of skin lesions ( Yuan et al., 2021 ). Given the functions of these key amino acids, the provision of a methionine- and choline-deficient diet could play a critical role in alteration of the structural and immunologic role of the skin, predisposing to the dermatologic lesions present in these animals.…”
Section: Discussionmentioning
confidence: 99%